Engineering Properties of Wheat and Corn Under Libya Conditions - Zubaydah Alzubayr (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Cereal grains are biological materials and as such have certain unique characteristics. The knowledge about the physical and mechanical properties of cereal grains is crucial for machine design, operational efficiency, and handling. Aerodynamic properties of solid materials have long been used to convey and separate seeds and grains during post-harvest operations. The experimental work was carried out during the year 2023 at the Agricultural Engineering Department, Faculty of Agriculture, Omar Al-Mokhtar University, Al-Beyda, Libya. The main objective of this research to determine and measurements of engineering properties including the physical, mechanical and aero-dynamic properties of wheat and corn beans grains under Libya conditions subjected to design the operating machines. Methods. The experimental work was carried out through 2023 at the Agricultural Engineering Department, Faculty of Agriculture, Omar Al-Mokhtar University, Al-Beyda, Libya, to verify the engineering properties of different seeds. Samples of wheat and corn grains were selected randomly (average of 100 grain crop) and cleaned by hand grains dimensions were tested under a moisture level of 8 %. The average of physical, mechanical and aerodynamic properties was determined for each studied grain. Results. It is clear that the value of geometric mean diameter recorded largest value of corn followed by wheat were 7.75 and 4.25 mm, respectively. The projected area of wheat and corn grains were 18.72, 82.09 mm2, respectively. Whereas, the porosity of wheat and corn were 42.09 and 32.36 %, respectively. The average angle of repose was largest of wheat followed by corn grains were 27.60 and 20.4o C, respectively. While, the coefficient of fraction largest of corn followed by wheat grains as 24.81 and 19.41 respectively. The terminal velocity, was largest of wheat followed by corn grains were 7.80 and 15.02 m/s, respectively. On the otherwise, the drag coefficient largest of corn and wheat grains of 0.30 and 0.61, respectively. Also, the Renold’s number largest of corn followed by wheat of 9592.03 and 2378.94, respectively. Conclusion. The results from these experiments on wheat and corn grains at 12 and 14 % moisture conducted the content dry basis revealed. The results showed that the pattern of air flow is in the range of turbulent flow. The develop designs to improve product quality and to increase energy efficiency.